2021
DOI: 10.1016/j.artd.2021.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Patient Resilience Has Moderate Correlation With Functional Outcomes, but Not Satisfaction, After Primary Unilateral Total Knee Arthroplasty

Abstract: Background: As many as 20% of patients who undergo total knee arthroplasty (TKA) are dissatisfied. Psychological factors have been shown to play a role in outcomes after TKA. The purpose of this study was to investigate the impact of patient resilience on functional outcomes and satisfaction after primary unilateral TKA. Methods: Eighty-six patients who underwent primary unilateral TKA by a single surgeon were studied. Primary outcomes were the Brief Resilience Scale (BRS), mental health component of the Veter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“… 3 , 10 , 16 A recent study evaluating total knee arthroplasty (TKA) patients showed that preoperative resilience is an important predictor of physical and mental health of patients at 3 months and 12 months postsurgery. 16 Further, greater concurrent resilience was associated with better scores across all measured outcomes, which is in contrast to a recent study of TKA patients by Haffar et al 8 which found no significant correlation between resilience and patient-reported outcome scores, both measured 1 year postoperatively. 16 In a similar study, Tokish et al 27 assessed 70 total shoulder arthroplasty (TSA) patients for a minimum of 2 years postoperatively and divided the patients into 3 groups based on Brief Resilience Scale (BRS) scores (low-resilience, normal-resilience, and high-resilience).…”
contrasting
confidence: 61%
“… 3 , 10 , 16 A recent study evaluating total knee arthroplasty (TKA) patients showed that preoperative resilience is an important predictor of physical and mental health of patients at 3 months and 12 months postsurgery. 16 Further, greater concurrent resilience was associated with better scores across all measured outcomes, which is in contrast to a recent study of TKA patients by Haffar et al 8 which found no significant correlation between resilience and patient-reported outcome scores, both measured 1 year postoperatively. 16 In a similar study, Tokish et al 27 assessed 70 total shoulder arthroplasty (TSA) patients for a minimum of 2 years postoperatively and divided the patients into 3 groups based on Brief Resilience Scale (BRS) scores (low-resilience, normal-resilience, and high-resilience).…”
contrasting
confidence: 61%
“…There have been numerous studies linking an individual’s resilience to their mental well-being, 40 , 41 , 42 , 43 , 44 as well as their expectations following a procedure. 45 , 46 , 47 Most of the differences seen between the groups were during the preoperative period and up to 1 year postoperatively, with comparable results seen at final follow-up among all groups. A possible explanation to this may be that lower resiliencies in those undergoing ACLR may affect short-term PROMs more than long-term PROMs because they are experiencing a more difficult time coping with the procedure itself and during the rehabilitation process.…”
Section: Discussionmentioning
confidence: 80%
“…Collectively, these studies have shown an association with higher resilience and superior physical function after surgery. 12 , 13 , 14 , 27 , 28 Among 152 patients with a hip fracture treated with surgery, Lim et al. 29 observed a positive correlation between preoperative resilience and higher physical function subscale scores on the Short Form-36 instrument.…”
Section: Discussionmentioning
confidence: 99%